2020
DOI: 10.3390/app10030919
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Network Alterations in Alzheimer’s Disease Patients

Abstract: Previous studies have revealed the occurrence of alterations of white matter (WM) and grey matter (GM) microstructures in Alzheimer’s disease (AD) and their prodromal state amnestic mild cognitive impairment (MCI). In general, these alterations can be studied comprehensively by modeling the brain as a complex network, which describes many important topological properties, such as the small-world property, modularity, and efficiency. In this study, we systematically investigated white matter abnormalities using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Network alterations of structural connections in participants with EMCI, LMCI and AD, compared with the HC group, were explored using NBS analysis. The results are consistent with previous findings that structural network disturbances begin in the limbic regions (Lama & Lee, 2020; Mallio et al, 2015). Furthermore, the present study provides additional insight into the time course of structural degradation.…”
Section: Discussionsupporting
confidence: 93%
“…Network alterations of structural connections in participants with EMCI, LMCI and AD, compared with the HC group, were explored using NBS analysis. The results are consistent with previous findings that structural network disturbances begin in the limbic regions (Lama & Lee, 2020; Mallio et al, 2015). Furthermore, the present study provides additional insight into the time course of structural degradation.…”
Section: Discussionsupporting
confidence: 93%
“…This opens up new possibilities for the multimodal imaging system to include the results of the H&Estained sample in the multimodal data evaluation for tissue research and diagnostic within ex-vivo applications. Those applications are not limited to the separation of GM and WM although structural changes within GM and/or WM are indicative for patients with HIV [85], multiple sclerosis [86], and Alzheimer's disease [87,88]. Ex-vivo applications of any tissue section for research and diagnostic purposes are possible.…”
Section: Discussionmentioning
confidence: 99%
“… 30 31 Local WM network disruption in the SMA and putamen has also been reported previously in AD. 32 The SMA is one of the neural correlates of verbal short-term memory in AD, 33 and the putamen has also been reported to be associated with cognitive impairment in AD. 34 A previous WM network study found decreased local efficiency in the right occipital area, 35 similarly to our results.…”
Section: Discussionmentioning
confidence: 99%